Curable resin composition containing maleimide resin and cured product thereof
By using a curable resin composition of maleimide resin and imidazole compound, the problem of unstable electrical performance of resin materials under high frequency and high temperature conditions is solved, and the effects of high thermal stability and low dielectric loss are achieved. It is suitable for lightweight and high-strength materials and 3D printing.
Patent Information
- Application Number
- JP2021098184
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-11
- Publication Date
- 2025-02-10
- Estimated Expiration
- 2041-06-11
AI Technical Summary
Existing resin materials are difficult to maintain good electrical properties under high frequency and high temperature conditions, and lack shape stability and mechanical properties in 3D printing applications.
The curable resin composition containing maleimide resin and imidazole compounds is used to improve the thermal stability and low dielectric properties of the resin by controlling the molecular structure and reaction conditions.
It achieves low dielectric loss and high thermal stability of resins under high temperature and high frequency conditions, and is suitable for lightweight, high-strength materials and 3D printing applications.
Smart Images

Figure 0007628371000005 
Figure 0007628371000006 
Figure 0007628371000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable resin composition containing a maleimide resin, and a cured product thereof, which is suitable for use in electrical and electronic components such as semiconductor encapsulants, printed wiring boards, and build-up laminates, lightweight, high-strength materials such as carbon fiber reinforced plastics and glass fiber reinforced plastics, and 3D printing applications. [Background technology]
[0002] In recent years, the required characteristics of laminates on which electric and electronic components are mounted have become more extensive and sophisticated due to the expansion of the fields in which they are used. Conventional semiconductor chips were mainly mounted on metal lead frames, but semiconductor chips with high processing power, such as central processing units (hereinafter referred to as CPUs), are increasingly being mounted on laminates made of polymer materials.
[0003] In particular, semiconductor packages (hereinafter referred to as PKG) used in smartphones and other devices require thinner PKG substrates to meet the demand for smaller size, thinner thickness, and higher density, but as the PKG substrate becomes thinner, its rigidity decreases, and defects such as large warping occur when the PKG is heated during solder mounting to the motherboard (PCB).To reduce this, there is a demand for PKG substrate materials with a high Tg above the solder mounting temperature.
[0004] In addition, the fifth generation communication system "5G", whose development is currently accelerating, is expected to further increase capacity and speed of communication. In 5G, the frequency used will become higher, and further performance improvement of the board material will be required to realize high-speed communication using high frequency. For example, it is important to have low dielectric properties to reduce transmission loss, and the dielectric tangent is required to be at least 0.005 or less at 10 GHz. The transmission loss that occurs on a printed circuit board is due to conductor loss and dielectric loss (Non-Patent Document 1). Conductor loss is caused by the resistance component of the conductor such as the wiring on the board, and is divided into loss due to the skin effect at high frequencies and scattering loss due to the roughness of the copper foil surface. Since the electric signal flows closer to the copper foil surface at higher frequencies (the distance from the copper foil surface is 1 GHz: 2.1 μm, 10 GHz: 0.66 μm), the copper foil roughness has been reduced in recent years to reduce the skin effect. For this reason, one of the requirements for resin materials is to ensure adhesion to low-roughness copper foil, but low-dielectric materials such as PTFE (polytetrafluoroethylene) and LCP (liquid crystal polymer) have poor adhesion, and because these materials are thermoplastic, they also have poor formability. In light of this, there is a demand for the development of thermosetting resins that have excellent adhesion, low dielectric properties, and formability.
[0005] In particular, in applications such as in-vehicle millimeter-wave radar, heat generation from chips mounted on wiring boards has become a problem. In addition, since wiring boards are exposed to high temperatures, such as junction temperatures exceeding 100°C, wiring boards are required to have stable electrical properties at high temperatures. For this reason, the substrate for wiring boards is required to be, for example, resistant to thermal degradation of dielectric properties (Patent Document 1).
[0006] Furthermore, with the advancement of electronics in the automotive field, precision electronic devices are sometimes placed near the engine drive, requiring higher levels of heat and moisture resistance.SiC semiconductors are beginning to be used in trains and air conditioners, and the encapsulation material for semiconductor elements is now required to have extremely high heat resistance, which is no longer possible with conventional epoxy resin encapsulation materials.
[0007] In light of this background, polymeric materials that can achieve both heat resistance and low dielectric tangent characteristics are being studied. For example, Patent Document 2 proposes a composition containing a maleimide resin and a propenyl group-containing phenolic resin. However, on the other hand, since phenolic hydroxyl groups that do not participate in the reaction remain during the curing reaction, the electrical properties are not sufficient. Patent Document 3 also discloses an allyl ether resin in which hydroxyl groups are substituted with allyl groups. However, it has been shown that Claisen rearrangement occurs at 190°C, and at 200°C, which is the molding temperature of a general substrate, phenolic hydroxyl groups that do not contribute to the curing reaction are generated, so the electrical properties are not satisfactory.
[0008] In recent years, 3D printing has been attracting attention as a method for three-dimensional modeling, and this 3D printing method is beginning to be applied in fields that require reliability, such as aerospace, automobiles, and even connectors for electronic components used in these. In particular, photocurable and thermosetting resins are being studied for applications such as stereolithography (SLA) and digital light processing (DLP). Therefore, while the main requirements for shape stability and accuracy were the traditional method of transferring from a mold, 3D printing applications require various properties such as heat resistance, mechanical properties, toughness, flame retardancy, and even electrical properties, and material development is being promoted. [Prior art documents] [Non-patent literature]
[0009] [Non-Patent Document 1] Signal loss factors in high-speed signal transmission on printed circuit boards (Mitsui Mining & Smelting Co., Ltd.) 29th Japan Institute of Electronics Packaging Spring Conference 16P1-17 [Patent documents]
[0010] [Patent Document 1] JP 2019-44090 A [Patent Document 2] Japanese Patent Application Publication No. 04-359911 [Patent Document 3] International Publication No. 2016 / 002704 Summary of the Invention [Problem to be solved by the invention]
[0011] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a curable resin composition containing a maleimide resin which exhibits excellent heat resistance and electrical properties, is resistant to thermal degradation of dielectric properties even after a high-temperature storage test, and has good curability, and a cured product thereof. [Means for solving the problem]
[0012] Means for Solving the Problems The present inventors conducted intensive research to solve the above problems and found that a cured product of a curable resin composition containing a maleimide resin has excellent heat resistance and low dielectric properties, and is less susceptible to thermal degradation of its dielectric properties even after a high-temperature storage test, thereby completing the present invention.
[0013] That is, the present invention relates to the following [1] to [6]. Note that in this application, "(Numerical value 1) to (Numerical value 2)" indicates that the upper and lower limits are included. [1] A curable resin composition containing a maleimide resin and an imidazole compound, the curable resin composition containing, as the maleimide resin, a maleimide compound represented by the following formula (1):
[0014] [ka]
[0015] [2] The curable resin composition according to the above item [1], wherein the imidazole compound is 2-ethyl-4-methylimidazole. [3] 3. The curable resin composition according to claim 1, wherein the maleimide resin is present in an amount of 90% by weight or more and 99.9% by weight or less in the total amount of the curable resin composition. [4] The curable resin composition according to any one of the above items [1] to [3], which is used for electric and electronic parts. [5] The curable resin composition according to any one of the preceding items [1] to [3], which is used for a lightweight, high-strength material application. [6] A cured product obtained by curing the curable resin composition according to any one of the above items [1] to [5]. Effect of the Invention
[0016] The curable resin composition of the present invention has excellent curability, and the cured product thereof has excellent properties such as high heat resistance and low dielectric properties. Therefore, the curable resin composition is useful for sealing electric and electronic components, circuit boards, carbon fiber composite materials, and other lightweight and high-strength materials. [Brief description of the drawings]
[0017] [Figure 1] 1 shows a GPC chart of Synthesis Example 1. [Diagram 2] 1H-NMR chart of Synthesis Example 1 is shown. [Diagram 3] 1 shows a GPC chart of Synthesis Example 2. [Figure 4] 1H-NMR chart of Synthesis Example 2 is shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The curable resin composition of the present invention contains a maleimide resin and an imidazole compound, and contains a maleimide compound represented by the following formula (1) as the maleimide resin.
[0019] [ka]
[0020] The maleimide compound represented by the formula (1) has two methyl groups on the aromatic ring, and therefore exhibits good dielectric properties and low water absorption. When there is only one methyl group, the symmetry of the molecule is broken, resulting in an asymmetry of polarization, which may adversely affect the dielectric properties, and the molecular rotation control effect may not be sufficiently obtained, resulting in a decrease in heat resistance. On the other hand, when there are three or more methyl groups, the methyl group itself may be oxidized by oxygen in the air in a high-temperature storage test (150°C, 24 hours or more, etc.) as the electron density on the aromatic ring increases due to the hyperconjugation effect, and aldehydes and carboxylic acids may be generated, which may lead to deterioration of the dielectric properties. In addition, when an alkyl group having a secondary or tertiary carbon other than the methyl group (such as an ethyl group or an isopropenyl group) is present on the aromatic ring, the hydrogen at the benzyl position, which has a higher electron density than the methyl group, is more likely to be oxidized. Since the substitution position of the methyl group is ortho-position to the maleimide group, the molecular rotation is controlled, and high heat resistance and good dielectric properties (low dielectric constant, low dielectric tangent) are exhibited.
[0021] The alkyl-substituted diaminodiphenylmethane, which is the raw material of the maleimide compound represented by the formula (1), is obtained by reacting alkyl-substituted aniline and formaldehyde. Any known method may be used as the reaction method, but for example, an aqueous hydrochloric acid solution is dropped in the presence of an excess amount of alkyl-substituted aniline to form an alkyl-substituted aniline hydrochloride. An aqueous formaldehyde solution is dropped thereto, and the reaction is carried out while distilling off water, followed by recrystallization to obtain the alkyl-substituted aniline. In this case, the molar ratio of the alkyl-substituted aniline to the formaldehyde is preferably 1.01 to 20, more preferably 1.1 to 15, and even more preferably 1.5 to 10. This is because the above range can prevent a significant decrease in the yield of the target product. In addition, examples of the acid catalyst used include hydrochloric acid, phosphoric acid, sulfuric acid, formic acid, p-toluenesulfonic acid, methanesulfonic acid, Lewis acids such as aluminum chloride and zinc chloride, solid acids such as activated clay, acid clay, white carbon, zeolite, and silica alumina, and acidic ion exchange resins. These may be used alone or in combination of two or more. The amount of catalyst used is usually 0.1 to 0.8 mol, preferably 0.2 to 0.7 mol, per mol of amino group of the amine compound used. If the amount of catalyst used is too large, the viscosity of the reaction solution may be too high, making stirring difficult, and if the amount is too small, the reaction may proceed slowly. During the reaction, a solvent may be used as necessary. For example, non-water-soluble solvents such as aromatic solvents such as toluene and xylene, aliphatic solvents such as cyclohexane and n-hexane, ethers such as diethyl ether and diisopropyl ether, ester solvents such as ethyl acetate and butyl acetate, and ketone solvents such as methyl isobutyl ketone and cyclopentanone may be used, but are not limited to these, and two or more may be used in combination. In addition to the non-water-soluble solvent, a non-protonic polar solvent can be used in combination. For example, dimethyl sulfone, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, 1,3-dimethyl-2-imidazolidinone, N-methylpyrrolidone, etc. can be mentioned, and two or more of them can be used in combination. When using a non-protonic polar solvent, it is preferable to use one with a higher boiling point than the non-water-soluble solvent to be used in combination. When hydrochloric acid, sulfonic acid, etc. are used as a catalyst, neutralization with an alkali metal such as sodium hydroxide or potassium hydroxide can be performed before proceeding to the extraction step. For the extraction step, an aromatic hydrocarbon solvent such as toluene or xylene can be used alone, or a non-aromatic hydrocarbon such as cyclohexane or toluene can be used in combination. After extraction, the organic layer is washed with water until the wastewater becomes neutral, and the solvent is distilled off using an evaporator, etc., to obtain the target amine compound. In addition, a recrystallization step can be performed as a purification step.
[0022] The method for producing the maleimide compound represented by the formula (1) is not particularly limited, but it can be derived from an alkyl-substituted diaminodiphenylmethane and maleic anhydride. Specifically, the target maleimide compound is obtained by reacting alkyl-substituted diaminodiphenylmethane with maleic anhydride in a solvent in the presence of a catalyst. Examples of the solvent to be used include, but are not limited to, non-water-soluble solvents such as aromatic solvents such as toluene and xylene, aliphatic solvents such as cyclohexane and n-hexane, ethers such as diethyl ether and diisopropyl ether, ester solvents such as ethyl acetate and butyl acetate, and ketone solvents such as methyl isobutyl ketone and cyclopentanone. Two or more of these may be used in combination. In addition to the non-water-soluble solvent, a non-protic polar solvent may also be used in combination. Examples include dimethyl sulfone, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, 1,3-dimethyl-2-imidazolidinone, and N-methylpyrrolidone, and two or more of these may be used in combination. When using an aprotic polar solvent, it is preferable to use one with a higher boiling point than the non-water-soluble solvent to be used in combination. In the reaction, if necessary, hydrochloric acid, phosphoric acid, sulfuric acid, formic acid, p-toluenesulfonic acid, methanesulfonic acid, Lewis acids such as aluminum chloride and zinc chloride, solid acids such as activated clay, acid clay, white carbon, zeolite, and silica alumina, and acidic ion exchange resins can be used as catalysts. These may be used alone or in combination of two or more. The amount of catalyst used is usually 0.1 to 0.8 mol, preferably 0.2 to 0.7 mol, per mol of amino group of the amine compound used. If the amount of catalyst used is too large, the viscosity of the reaction solution may be too high, making stirring difficult, and if the amount is too small, the reaction may proceed slowly. In addition, as a co-catalyst for imidization, a basic co-catalyst such as triethylamine may be used alone or in combination. When sulfonic acid or the like is used as a catalyst, it may be neutralized with an alkali metal such as sodium hydroxide or potassium hydroxide before proceeding to the extraction step. For the extraction step, an aromatic hydrocarbon solvent such as toluene or xylene may be used alone, or a non-aromatic hydrocarbon such as cyclohexane or toluene may be used in combination. After extraction, the organic layer is washed with water until the wastewater becomes neutral, and the solvent is removed using an evaporator or the like to obtain the target maleimide compound. A recrystallization step may also be carried out as a purification step.
[0023] The maleimide resin of the present invention may contain a maleimide resin other than the maleimide compound represented by the formula (1). Examples of the maleimide resin other than the maleimide compound represented by the formula (1) include 4,4'-diphenylmethane bismaleimide, polyphenylmethane maleimide, m-phenylene bismaleimide, 2,2'-bis[4-(4-maleimidophenoxy)phenyl]propane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, 4,4'-diphenylether bismaleimide, 4,4'-diphenylsulfone bismaleimide, 1,3-bis(3-maleimidophenoxy)benzene, 1,3-bis(4-maleimidophenoxy)benzene), Xylox type maleimide resin (anilix), maleimide, manufactured by Mitsui Chemicals Fine Co., Ltd.), biphenylaralkyl-type maleimide resin (solidified by distilling off the solvent under reduced pressure from a resin solution containing the maleimide resin (M2) described in Example 4 of JP 2009-001783 A), and bisaminocumylbenzene-type maleimide (maleimide resin described in WO 2020 / 054601 A).
[0024] The maleimide resin of the present invention preferably contains the maleimide compound represented by formula (1) in an amount of 50% by weight or more and 100% by weight or less, and more preferably 80% by weight or more and 100% by weight or less, based on the total amount of the maleimide resin. This is because the above content of the maleimide compound represented by formula (1) allows the properties of the maleimide compound represented by formula (1) to be fully exhibited.
[0025] The maleimide resin is preferably contained in an amount of 90% by weight or more and 99.9% by weight or less, and more preferably 95% by weight or more and 99.5% by weight or less, based on the total amount of the curable resin composition, because the above content of the maleimide resin allows the properties of the maleimide resin to be fully exhibited.
[0026] The curable resin composition of the present invention contains an imidazole compound for the purpose of curing the maleimide resin. Examples of the imidazole compound include 2-methylimidazole, 2-ethylimidazole, and 2-ethyl-4-methylimidazole. The amount of the imidazole compound is preferably 0.1 parts by weight or more and 10 parts by weight or less, and more preferably 0.5 parts by weight or more and 5 parts by weight or less, based on the total amount of the curable resin composition. The imidazole catalyst is preferred because it is easier to control the curing rate compared to thermal radical polymerization initiators such as peroxide compounds such as dicumyl peroxide. When a peroxide compound is used as a catalyst, it is difficult to adjust the degree of curing during prepreg formation, and it is difficult to obtain a prepreg in a B-stage state with the desired degree of polymerization. In addition, when an imidazole catalyst is used, it is also preferred because it can be used in combination with epoxy resins, which are widely used as general-purpose resins. By adding epoxy resins, etc., it is possible to improve adhesion and mechanical strength of the cured product (bending strength, crack resistance, etc.).
[0027] In the curable resin composition of the present invention, in addition to the imidazole compound, a curing accelerator (curing catalyst) may be used in combination to improve the curability. As the curing accelerator that can be used, it is preferable to use a radical polymerization initiator.
[0028] Examples of the radical polymerization initiator include ketone peroxides such as methyl ethyl ketone peroxide and acetylacetone peroxide, diacyl peroxides such as benzoyl peroxide, dialkyl peroxides such as dicumyl peroxide and 1,3-bis-(t-butylperoxyisopropyl)-benzene, peroxyketals such as t-butyl peroxybenzoate and 1,1-di-t-butylperoxycyclohexane, α-cumyl peroxyneodecanoate, t-butyl peroxyneodecanoate, t-butyl peroxypivalate, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, t-amylperoxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, and t-amylperoxy-3,5,5-trimethylhexanoate. peroxycarbonates such as di-2-ethylhexyl peroxydicarbonate, bis(4-t-butylcyclohexyl)peroxydicarbonate, t-butylperoxyisopropyl carbonate, 1,6-bis(t-butylperoxycarbonyloxy)hexane; organic peroxides such as t-butyl hydroperoxide, cumene hydroperoxide, t-butyl peroxyoctoate, lauroyl peroxide; and known curing accelerators such as azo compounds such as azobisisobutyronitrile, 4,4'-azobis(4-cyanovaleric acid), and 2,2'-azobis(2,4-dimethylvaleronitrile). However, the curing accelerator is not particularly limited to these. Ketone peroxides, diacyl peroxides, hydroperoxides, dialkyl peroxides, peroxyketals, alkyl peresters, percarbonates, etc. are preferred, and dialkyl peroxides are more preferred.
[0029] If necessary, a curing accelerator other than the imidazole compound or the radical polymerization initiator may be added or used in combination. Specific examples of the curing accelerator that can be used include tertiary amines such as 2-(dimethylaminomethyl)phenol and 1,8-diaza-bicyclo(5,4,0)undecene-7, phosphines such as triphenylphosphine, quaternary ammonium salts such as tetrabutylammonium salt, triisopropylmethylammonium salt, trimethyldecanylammonium salt, cetyltrimethylammonium salt, and hexadecyltrimethylammonium hydroxide, quaternary phosphonium salts such as triphenylbenzylphosphonium salt, triphenylethylphosphonium salt, and tetrabutylphosphonium salt (the counter ion of the quaternary salt is a halogen, an organic acid ion, a hydroxide ion, etc., and is not particularly specified, but an organic acid ion and a hydroxide ion are particularly preferred.), transition metal compounds (transition metal salts) such as zinc compounds such as tin octylate, zinc carboxylate (zinc 2-ethylhexanoate, zinc stearate, zinc behenate, zinc myristylate), and zinc phosphate ester (zinc octyl phosphate, zinc stearyl phosphate, etc.), and the like.
[0030] The curable composition of the present invention may contain a polymerization inhibitor. By containing a polymerization inhibitor, storage stability is improved and the reaction initiation temperature can be controlled. By controlling the reaction initiation temperature, it becomes easy to ensure fluidity, impregnation into glass cloth and the like is not impaired, and B-stage such as prepreg formation is facilitated. If the polymerization reaction proceeds too much during prepreg formation, problems such as difficulty in lamination during the lamination process are likely to occur. Examples of polymerization inhibitors that can be used include phenol-based, sulfur-based, phosphorus-based, hindered amine-based, nitroso-based, and nitroxyl radical-based polymerization inhibitors. The polymerization inhibitor may be added when synthesizing the maleimide compound represented by the formula (1) or after the synthesis. The polymerization inhibitors may be used alone or in combination of two or more. The amount of the polymerization inhibitor used is usually 0.008 to 1 part by weight, preferably 0.01 to 0.5 parts by weight, based on 100 parts by weight of the resin component. These polymerization inhibitors may be used alone or in combination of two or more. In the present invention, phenol-based, hindered amine-based, nitroso-based, and nitroxyl radical-based are preferred.
[0031] Specific examples of phenol-based polymerization inhibitors include 2,6-di-t-butyl-p-cresol, butylated hydroxyanisole, 2,6-di-t-butyl-p-ethylphenol, stearyl-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, isooctyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2,4-bis-(n-octylthio)-6-(4-hydroxy-3, Monophenols such as 5-di-t-butylanilino)-1,3,5-triazine, 2,4-bis[(octylthio)methyl]-o-cresol, etc.; 2,2'-methylenebis(4-methyl-6-t-butylphenol), 2,2'-methylenebis(4-ethyl-6-t-butylphenol), 4,4'-thiobis(3-methyl-6-t-butylphenol), 4,4'-butylidenebis(3-methyl-6-t-butylphenol), Triethylene glycol-bis[3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,6-hexanediol-bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], N,N'-hexamethylenebis(3,5-di-t-butyl-4-hydroxy-hydrocinnamamide), 2,2-thio-diethylenebis[3-(3,5-di-t-butyl-4-hydroxyphenyl ) propionate], 3,5-di-t-butyl-4-hydroxybenzylphosphonate-diethyl ester, 3,9-bis[1,1-dimethyl-2-{β-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy}ethyl]2,4,8,10-tetraoxaspiro[5,5]undecane, bis(3,5-di-t-butyl-4-hydroxybenzylsulfonate ethyl)calcium and other bisphenols;Examples of polymeric phenols include 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane, bis[3,3'-bis-(4'-hydroxy-3'-t-butylphenyl)butyric acid]glycol ester, tris-(3,5-di-t-butyl-4-hydroxybenzyl)-isocyanurate, 1,3,5-tris(3',5'-di-t-butyl-4'-hydroxybenzyl)-S-triazine-2,4,6-(1H,3H,5H)trione, and tocopherol.
[0032] Specific examples of sulfur-based polymerization inhibitors include dilauryl-3,3'-thiodipropionate, dimyristyl-3,3'-thiodipropionate, distearyl-3,3'-thiodipropionate, and the like.
[0033] Specific examples of phosphorus-based polymerization inhibitors include triphenyl phosphite, diphenyl isodecyl phosphite, phenyl diisodecyl phosphite, tris(nonylphenyl)phosphite, diisodecyl pentaerythritol phosphite, tris(2,4-di-t-butylphenyl)phosphite, cyclic neopentane tetraylbis(octadecyl)phosphite, cyclic neopentane tetraylbi(2,4-di-t-butylphenyl)phosphite, and cyclic neopentane tetraylbi(2,4-di-t-butyl-4-methylphenyl)phosphite. and phosphites such as bis[2-t-butyl-6-methyl-4-{2-(octadecyloxycarbonyl)ethyl}phenyl]hydrogen phosphite; and oxaphosphaphenanthrene oxides such as 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(3,5-di-t-butyl-4-hydroxybenzyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 10-decyloxy-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.
[0034] Specific examples of the hindered amine polymerization inhibitor include, but are not limited to, Adeka STAB LA-40MP, Adeka STAB LA-40Si, Adeka STAB LA-402AF, Adeka STAB LA-87, Deka STAB LA-82, Deka STAB LA-81, Adeka STAB LA-77Y, Adeka STAB LA-77G, Adeka STAB LA-72, Adeka STAB LA-68, Adeka STAB LA-63P, Adeka STAB LA-57, Adeka STAB LA-52, Chimassorb 2020FDL, Chimassorb 944FDL, Chimassorb 944LD, Tinuvin 622SF, Tinuvin PA144, Tinuvin 765, Tinuvin 770DF, Tinuvin XT55FB, Tinuvin 111FDL, Tinuvin 783FDL, Tinuvin 791FB, and the like.
[0035] Specific examples of the nitroso-based polymerization inhibitor include p-nitrosophenol, N-nitrosodiphenylamine, and the ammonium salt of N-nitrosophenylhydroxyamine (cupferron), with the ammonium salt of N-nitrosophenylhydroxyamine (cupferron) being preferred.
[0036] Specific examples of nitroxyl radical polymerization inhibitors include, but are not limited to, di-tert-butyl nitroxide, 2,2,6,6-tetramethylpiperidine-1-oxyl, 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-oxo-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-amino-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-methoxy-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-acetoxy-2,2,6,6-tetramethylpiperidine-1-oxyl, and 4-benzoyloxy-2,2,6,6-tetramethylpiperidine-1-oxyl.
[0037] The curable resin composition of the present invention may use any known material as a curable resin other than maleimide resin. Specifically, phenol resin, epoxy resin, amine resin, active alkene-containing resin, isocyanate resin, polyamide resin, polyimide resin, cyanate ester resin, propenyl resin, methallyl resin, active ester resin, etc. may be used alone or in combination. In addition, it is preferable to contain an epoxy resin, an active alkene-containing resin, or a cyanate ester resin from the perspective of the balance of heat resistance, adhesion, and dielectric properties. By containing these curable resins, the brittleness of the cured product and adhesion to metals can be improved, and cracks in the package during solder reflow and reliability tests such as thermal cycles can be suppressed. The amount of the curable resin used is preferably 10 times by mass or less, more preferably 5 times by mass or less, and particularly preferably 3 times by mass or less, relative to the amount of the maleimide resin. The lower limit is preferably 0.5 times by mass or more, and more preferably 1 time by mass or more. If the amount is 10 times by mass or less, the effects of the heat resistance and dielectric properties of the maleimide resin can be utilized.
[0038] As the phenol resin, epoxy resin, amine resin, active alkene-containing resin, isocyanate resin, polyamide resin, polyimide resin, cyanate ester resin, and active ester resin, the following examples can be used.
[0039] Phenolic resins: Polycondensates of phenols (phenol, alkyl-substituted phenols, aromatic-substituted phenols, hydroquinone, resorcin, naphthol, alkyl-substituted naphthol, dihydroxybenzene, alkyl-substituted dihydroxybenzene, dihydroxynaphthalene, etc.) and various aldehydes (formaldehyde, acetaldehyde, alkyl aldehyde, benzaldehyde, alkyl-substituted benzaldehyde, hydroxybenzaldehyde, naphthaldehyde, glutaraldehyde, phthalaldehyde, crotonaldehyde, cinnamaldehyde, furfural, etc.), polycondensates of phenols and various diene compounds (dicyclopentadiene, terpenes, vinylcyclohexene, norbornadiene, vinylnorbornene, tetrahydrofuran, etc.), phenols and ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, acetophenone, benzophenone, etc.); phenol resins obtained by polycondensation of phenols and substituted biphenyls (4,4'-bis(chloromethyl)-1,1'-biphenyl and 4,4'-bis(methoxymethyl)-1,1'-biphenyl, etc.) or substituted phenyls (1,4-bis(chloromethyl)benzene, 1,4-bis(methoxymethyl)benzene and 1,4-bis(hydroxymethyl)benzene, etc.); polycondensates of bisphenols and various aldehydes; and polyphenylene ether compounds.
[0040] Any known polyphenylene ether compound may be used, but from the viewpoint of heat resistance and electrical properties, it is preferable to use a polyphenylene ether compound having an ethylenically unsaturated double bond, and more preferably a polyphenylene ether compound having an acrylic group, a methacrylic group, or a styrene structure. Commercially available products include SA-9000-111 (manufactured by SABIC, a polyphenylene ether compound having a methacrylic group) and OPE-2St 1200 (manufactured by Mitsubishi Gas Chemical, a polyphenylene ether compound having a styrene structure). The number average molecular weight (Mn) of the polyphenylene ether compound is preferably 500 to 5000, more preferably 2000 to 5000, and more preferably 2000 to 4000. If the molecular weight is less than 500, the heat resistance of the cured product tends to be insufficient. If the molecular weight is more than 5000, the melt viscosity increases and sufficient fluidity cannot be obtained, which tends to lead to molding defects. In addition, the reactivity decreases, the curing reaction takes a long time, and the amount of unreacted material that is not incorporated into the curing system increases, which decreases the glass transition temperature of the cured product and tends to decrease the heat resistance of the cured product. If the number average molecular weight of the polyphenylene ether compound is 500 to 5000, it is possible to exhibit excellent heat resistance, moldability, etc. while maintaining excellent dielectric properties. The number average molecular weight here can be specifically measured using gel permeation chromatography, etc.
[0041] The polyphenylene ether compound may be one obtained by a polymerization reaction, or one obtained by a redistribution reaction of a high molecular weight polyphenylene ether compound having a number average molecular weight of about 10,000 to 30,000. In addition, these may be used as raw materials and reacted with a compound having an ethylenically unsaturated double bond, such as methacryl chloride, acrylic chloride, or chloromethylstyrene, to impart radical polymerizability. The polyphenylene ether compound obtained by the redistribution reaction is obtained, for example, by heating a high molecular weight polyphenylene ether compound in a solvent such as toluene in the presence of a phenolic compound and a radical initiator to cause a redistribution reaction. The polyphenylene ether compound obtained by the redistribution reaction in this way has hydroxyl groups derived from a phenolic compound that contributes to curing at both ends of the molecular chain, and is therefore preferable in that it can maintain even higher heat resistance, and that functional groups can be introduced at both ends of the molecular chain even after modification with a compound having an ethylenically unsaturated double bond. In addition, the polyphenylene ether compound obtained by the polymerization reaction is preferable in that it exhibits excellent fluidity.
[0042] The molecular weight of the polyphenylene ether compound can be adjusted by adjusting the polymerization conditions, etc., in the case of a polyphenylene ether compound obtained by a polymerization reaction. In addition, in the case of a polyphenylene ether compound obtained by a redistribution reaction, the molecular weight of the obtained polyphenylene ether compound can be adjusted by adjusting the conditions of the redistribution reaction, etc. More specifically, it is possible to adjust the amount of the phenolic compound used in the redistribution reaction. That is, the greater the amount of the phenolic compound, the lower the molecular weight of the obtained polyphenylene ether compound. In this case, poly(2,6-dimethyl-1,4-phenylene ether) and the like can be used as the high molecular weight polyphenylene ether compound that undergoes the redistribution reaction. In addition, the phenolic compound used in the redistribution reaction is not particularly limited, but for example, a multifunctional phenolic compound having two or more phenolic hydroxyl groups in the molecule, such as bisphenol A, phenol novolac, cresol novolac, etc., is preferably used. These may be used alone or in combination of two or more.
[0043] The content of the polyphenylene ether compound is not particularly limited, but is preferably 10 to 90 mass%, more preferably 20 to 80 mass%, based on the total mass of the curable resin components. When the content of the polyphenylene ether compound is 10 to 90 mass%, it is preferable in that a cured product is obtained that is not only excellent in heat resistance, but also fully exhibits the excellent dielectric properties of the polyphenylene ether compound.
[0044] Epoxy resins: glycidyl ether-based epoxy resins obtained by glycidylating the above-mentioned phenol resins and alcohols, alicyclic epoxy resins such as 4-vinyl-1-cyclohexene diepoxide and 3,4-epoxycyclohexylmethyl-3,4'-epoxycyclohexanecarboxylate, glycidyl amine-based epoxy resins such as tetraglycidyldiaminodiphenylmethane (TGDDM) and triglycidyl-p-aminophenol, and glycidyl ester-based epoxy resins.
[0045] Amine resins: diaminodiphenylmethane, diaminodiphenylsulfone, isophoronediamine, naphthalenediamine, aniline novolak, orthoethylaniline novolak, aniline resins obtained by reacting aniline with xylylene chloride, aniline and substituted biphenyls (4,4'-bis(chloromethyl)-1,1'-biphenyl, 4,4'-bis(methoxymethyl)-1,1'-biphenyl, etc.) or substituted phenyls (1,4-bis(chloromethyl)benzene, 1,4-bis(methoxymethyl)benzene, 1,4-bis(hydroxymethyl)benzene, etc.) described in Japanese Patent No. 6429862.
[0046] Active alkene-containing resin: polycondensation products of the above-mentioned phenol resin and an active alkene-containing halogen-based compound (chloromethylstyrene, allyl chloride, methallyl chloride, acrylic acid chloride, allyl chloride, etc.), polycondensation products of active alkene-containing phenols (2-allylphenol, 2-propenylphenol, 4-allylphenol, 4-propenylphenol, eugenol, isoeugenol, etc.) and a halogen-based compound (4,4'-bis(methoxymethyl)-1,1'-biphenyl, 1,4-bis(chloromethyl)benzene, 4,4'-difluorobenzophenone, 4,4'-dichlorobenzophenone, 4,4'-dibromobenzophenone, cyanuric chloride, etc.), polycondensation products of epoxy resins or alcohols and substituted or unsubstituted acrylates (acrylate, methacrylate, etc.).
[0047] Isocyanate resins: aromatic diisocyanates such as p-phenylene diisocyanate, m-phenylene diisocyanate, p-xylylene diisocyanate, m-xylylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, and naphthalene diisocyanate; aliphatic or alicyclic diisocyanates such as isophorone diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, hydrogenated xylene diisocyanate, norbornene diisocyanate, and lysine diisocyanate; polyisocyanates such as one or more biuret forms of isocyanate monomers or isocyanate forms obtained by trimerizing the above diisocyanate compounds; and polyisocyanates obtained by a urethanization reaction between the above isocyanate compounds and polyol compounds.
[0048] Polyamide resins: amino acids (6-aminocaproic acid, 11-aminoundecanoic acid, 12-aminododecanoic acid, p-aminomethylbenzoic acid, etc.), lactams (ε-caprolactam, ω-undecanelactam, ω-laurolactam), and aliphatic diamines such as diamines (ethylenediamine, trimethylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decanediamine, undecanediamine, dodecanediamine, tridecanediamine, tetradecanediamine, pentadecanediamine, hexadecanediamine, heptadecanediamine, octadecanediamine, nonadecanediamine, eicosanediamine, 2-methyl-1,5-diaminopentane, 2-methyl-1,8-diaminooctane, etc. Polymers made primarily from one or more of the following: alicyclic diamines such as cyclohexanediamine, bis-(4-aminocyclohexyl)methane, bis(3-methyl-4-aminocyclohexyl)methane; aromatic diamines such as xylylenediamine; and mixtures of dicarboxylic acids (aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, and dodecanedioic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 2-chloroterephthalic acid, 2-methylterephthalic acid, 5-methylisophthalic acid, 5-sodiumsulfoisophthalic acid, hexahydroterephthalic acid, and hexahydroisophthalic acid; alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid; dialkyl esters of these dicarboxylic acids, and dichlorides).
[0049] Polyimide resin: the above diamine and tetracarboxylic dianhydride (4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-cyclohexene-1,2 dicarboxylic anhydride, pyromellitic dianhydride, 1,2,3,4-benzenetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-di Phenylsulfonetetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, methylene-4,4'-diphthalic dianhydride, 1,1-ethylidene-4,4'-diphthalic dianhydride, 2,2'-propylidene-4,4'-diphthalic dianhydride, 1,2-ethylene-4,4'-diphthalic dianhydride, 1,3-trimethylene-4,4'-diphthalic dianhydride, 1,4-tetramethylene-4,4'-diphthalic dianhydride, 1,5-pentamethylene-4,4'-diphthalic dianhydride, 4,4'-oxydiphthalic dianhydride, thio-4,4 '-Diphthalic dianhydride, Sulfonyl-4,4'-diphthalic dianhydride, 1,3-bis(3,4-dicarboxyphenyl)benzene dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,3-bis[2-(3,4-dicarboxyphenyl)-2-propyl]benzene dianhydride, 1,4-bis[2-(3,4-dicarboxyphenyl)-2-propyl]benzene dianhydride, Bis[3-(3,4-dicarboxyphenoxy)phenyl]methane dianhydride, Bis [4-(3,4-dicarboxyphenoxy)phenyl]methane dianhydride, 2,2-bis[3-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, bis(3,4-dicarboxyphenoxy)dimethylsilane dianhydride, 1,3-bis(3,4-dicarboxyphenyl)-1,1,3,3-tetramethyldisiloxane dianhydride, 2,3,6,7-naphthalenetetracarboxylic acid dianhydride, 1,4,5,8-naphthalenetetracarboxylic acid dianhydride, 1,2,5,6-Naphthalenetetracarboxylic dianhydride, 3,4,9,10-Perylenetetracarboxylic dianhydride, 2,3,6,7-Anthracenetetracarboxylic dianhydride, 1,2,7,8-Phenanthrenetetracarboxylic dianhydride, Ethylenetetracarboxylic dianhydride, 1,2,3,4-Butanetetracarboxylic dianhydride, 1,2,3,4-Cyclobutanetetracarboxylic dianhydride, Cyclopentanetetracarboxylic dianhydride, Cyclohexane-1,2,3,4-tetracarboxylic dianhydride , cyclohexane-1,2,4,5-tetracarboxylic dianhydride, 3,3',4,4'-bicyclohexyltetracarboxylic dianhydride, carbonyl-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, methylene-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, 1,2-ethylene-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, 1,1-ethylidene-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, 2,2-Propylidene-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, oxy-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, thio-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, sulfonyl-4,4'-bis(cyclohexane-1,2-dicarboxylic acid) dianhydride, bicyclo[2,2,2]oct-7-ene-2,3,5,6-tetracarboxylic acid dianhydride, rel-[1S,5R,6R]-3-oxabicyclo[3 ,2,1]Octane-2,4-dione-6-spiro-3'-(tetrahydrofuran-2',5'-dione), 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride, ethylene glycol-bis-(3,4-dicarboxylic anhydride phenyl) ether, 4,4'-biphenyl bis(trimellitic acid monoester acid anhydride), 9,9'-bis(3,4-dicarboxyphenyl)fluorene dianhydride) polycondensate.
[0050] Cyanate ester resin: A cyanate ester compound obtained by reacting a phenolic resin with a cyanogen halide. Specific examples include, but are not limited to, dicyanatobenzene, tricyanatobenzene, dicyanatonaphthalene, dicyanatobiphenyl, 2,2'-bis(4-cyanatophenyl)propane, bis(4-cyanatophenyl)methane, bis(3,5-dimethyl-4-cyanatophenyl)methane, 2,2'-bis(3,5-dimethyl-4-cyanatophenyl)propane, 2,2'-bis(4-cyanatophenyl)ethane, 2,2'-bis(4-cyanatophenyl)hexafluoropropane, bis(4-cyanatophenyl)sulfone, bis(4-cyanatophenyl)thioether, phenol novolac cyanate, and phenol-dicyclopentadiene co-condensates in which the hydroxyl groups have been converted to cyanate groups. Furthermore, the cyanate ester compound, the synthesis method of which is described in JP-A-2005-264154, is particularly preferred as the cyanate ester compound because it has low moisture absorption, excellent flame retardancy, and excellent dielectric properties. The cyanate ester resin may contain a catalyst such as zinc naphthenate, cobalt naphthenate, copper naphthenate, lead naphthenate, zinc octoate, tin octoate, lead acetylacetonate, dibutyltin maleate, etc., to trimerize the cyanate group and form a sym-triazine ring, if necessary. The catalyst is usually used in an amount of 0.0001 to 0.10 parts by mass, preferably 0.00015 to 0.0015 parts by mass, per 100 parts by mass of the total mass of the curable resin composition.
[0051] Active ester resin: A compound having one or more active ester groups in one molecule can be used as a curing agent for a curable resin other than the maleimide compound represented by the formula (1), such as an epoxy resin, if necessary. As the active ester curing agent, a compound having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, is preferred. The active ester curing agent is preferably one obtained by a condensation reaction between at least one compound of a carboxylic acid compound and a thiocarboxylic acid compound and at least one compound of a hydroxy compound and a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester curing agent obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester curing agent obtained from a carboxylic acid compound and at least one compound of a phenol compound and a naphthol compound is preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid. Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol. Preferred specific examples of the active ester curing agent include an active ester compound containing a dicyclopentadiene-type diphenol structure, an active ester compound containing a naphthalene structure, an active ester compound containing an acetylated product of phenol novolac, and an active ester compound containing a benzoylated product of phenol novolac. Among them, an active ester compound containing a naphthalene structure and an active ester compound containing a dicyclopentadiene-type diphenol structure are more preferred. The "dicyclopentadiene-type diphenol structure" refers to a divalent structural unit consisting of phenylene-dicyclopentylene-phenylene. Commercially available active ester curing agents include, for example, active ester compounds containing a dicyclopentadiene-type diphenol structure, such as "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T", "HPC-8000H-65TM", "EXB-8000L-65TM", and "EXB-8150-65T" (manufactured by DIC Corporation); active ester compounds containing a naphthalene structure, such as "EXB9416-70BK" (manufactured by DIC Corporation); and phenolic Examples of active ester compounds containing an acetylated phenol novolac include "DC808" (manufactured by Mitsubishi Chemical Corporation); active ester compounds containing a benzoylated phenol novolac include "YLH1026", "YLH1030", and "YLH1048" (manufactured by Mitsubishi Chemical Corporation); "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester curing agent which is an acetylated phenol novolac; and "EXB-9050L-62M" (manufactured by DIC Corporation) as an active ester curing agent containing a phosphorus atom.
[0052] The curable resin composition of the present invention may contain a phosphorus-containing compound as a flame retardant-imparting component. The phosphorus-containing compound may be of either a reactive type or an additive type. Specific examples of the phosphorus-containing compound include phosphoric acid esters such as trimethyl phosphate, triethyl phosphate, tricresyl phosphate, trixylyleneyl phosphate, cresyl diphenyl phosphate, cresyl-2,6-dixylyleneyl phosphate, 1,3-phenylene bis(dixylyleneyl phosphate), 1,4-phenylene bis(dixylyleneyl phosphate), and 4,4'-biphenyl(dixylyleneyl phosphate); 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10(2,5- Phosphanes such as dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide; phosphorus-containing epoxy compounds obtained by reacting epoxy resins with active hydrogen of the phosphanes, red phosphorus, etc. are mentioned, but phosphates, phosphanes or phosphorus-containing epoxy compounds are preferred, and 1,3-phenylenebis(dixylyl phosphate), 1,4-phenylenebis(dixylyl phosphate), 4,4'-biphenyl(dixylyl phosphate) or phosphorus-containing epoxy compounds are particularly preferred. The content of the phosphorus-containing compound is preferably in the range of 0.1 to 0.6 (weight ratio) (phosphorus-containing compound) / (total epoxy resin). If it is 0.1 or less, the flame retardancy is insufficient, and if it is 0.6 or more, there is a concern that it may have an adverse effect on the moisture absorption and dielectric properties of the cured product.
[0053] Furthermore, a light stabilizer may be added to the curable resin composition of the present invention, if necessary. As the light stabilizer, a hindered amine light stabilizer, particularly HALS, etc., is preferable. Although there is no particular limitation on the HALS, representative examples include polycondensates of dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidyl)butylamine, polycondensates of dimethyl succinate-1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine, poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl) dimethyl)imino}], bis(1,2,2,6,6-pentamethyl-4-piperidyl) [[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, 2-(3,5-di-t-butyl-4-hydroxybenzyl)-2-n-butylmalonate bis(1,2,2,6,6-pentamethyl-4-piperidyl), etc. Only one type of HALS may be used, or two or more types may be used in combination.
[0054] Furthermore, the curable resin composition of the present invention may contain a binder resin as required. Examples of the binder resin include, but are not limited to, butyral resins, acetal resins, acrylic resins, epoxy-nylon resins, NBR-phenol resins, epoxy-NBR resins, polyamide resins, polyimide resins, and silicone resins. The amount of the binder resin is preferably within a range that does not impair the flame retardancy and heat resistance of the cured product, and is preferably 0.05 to 50 parts by mass, more preferably 0.05 to 20 parts by mass, based on 100 parts by mass of the resin component, as required.
[0055] Furthermore, to the curable resin composition of the present invention, powders such as fused silica, crystalline silica, porous silica, alumina, zircon, calcium silicate, calcium carbonate, quartz powder, silicon carbide, silicon nitride, boron nitride, zirconia, aluminum nitride, graphite, forsterite, steatite, spinel, mullite, titania, talc, clay, iron oxide asbestos, glass powder, etc., or inorganic fillers obtained by making these into a spherical or crushed shape, can be added as necessary. In particular, when a curable resin composition for semiconductor encapsulation is obtained, the amount of the inorganic filler used is usually 80 to 92% by mass, preferably 83 to 90% by mass, in the curable resin composition.
[0056] The curable resin composition of the present invention may contain known additives as necessary. Specific examples of additives that can be used include polybutadiene and modified products thereof, modified products of acrylonitrile copolymers, polyphenylene ether, polystyrene, polyethylene, polyimide, fluororesin, silicone gel, silicone oil, surface treatment agents for fillers such as silane coupling agents, mold release agents, and colorants such as carbon black, phthalocyanine blue, and phthalocyanine green. The amount of these additives to be added is preferably 1,000 parts by mass or less, more preferably 700 parts by mass or less, relative to 100 parts by mass of the curable resin composition. From the viewpoints of low water absorption and electrical properties, polybutadiene and modified products thereof, polyphenylene ether, polystyrene, polyethylene, fluororesin, etc. are preferred. From the viewpoints of electrical properties, adhesion, and low water absorption, polybutadiene and modified products thereof are preferred. Specific examples of the thermoplastic elastomer include butadiene-based elastomers such as styrene-butadiene copolymers (SBR: RICON-100, RICON-181, RICON-184, all manufactured by Cray Valley, etc.), acrylonitrile-butadiene copolymers, etc., and styrene-based thermoplastic elastomers such as styrene-butadiene-styrene copolymers (SBS), hydrogenated styrene-butadiene-styrene copolymers, styrene-isoprene-styrene copolymers (SIS), hydrogenated styrene-isoprene-styrene copolymers, and hydrogenated styrene-(butadiene / isoprene)-styrene copolymers. These styrene-based thermoplastic elastomers may be used alone or in combination of two or more kinds. Among these high molecular weight materials, styrene-based thermoplastic elastomers such as styrene-butadiene-styrene copolymer, hydrogenated styrene-butadiene-styrene copolymer, styrene-isoprene-styrene copolymer, hydrogenated styrene-isoprene-styrene copolymer, and hydrogenated styrene-(butadiene / isoprene)-styrene copolymer are preferred, and in particular, styrene-isoprene-styrene copolymer, hydrogenated styrene-butadiene-styrene copolymer, hydrogenated styrene-isoprene-styrene copolymer, and hydrogenated styrene-(butadiene / isoprene)-styrene copolymer are more preferred because they have higher heat resistance and are less susceptible to oxidative degradation.Specifically, Septon 1020, Septon 2002, Septon 2004F, Septon 2005, Septon 2006, Septon 2063, Septon 2104, Septon 4003, Septon 4044, Septon 4055, Septon 4077, Septon 4099, Septon 8004, Septon 8006, Septon 8007L, Septon HG252, Septon V9827, Hybler 7125 (hydrogenated), Hybler 7215F, and Hybler 7311F (all manufactured by Kuraray Co., Ltd.). In addition, the weight average molecular weight of the styrene-based thermoplastic elastomer is not particularly limited as long as it is 10,000 or more, but if it is too large, compatibility with not only the polyphenylene ether compound but also low molecular weight components having a weight average molecular weight of about 50 to 1,000 and oligomer components having a weight average molecular weight of about 1,000 to 5,000 deteriorates, making it difficult to ensure mixing and solvent stability, so that it is preferably about 10,000 to 300,000.
[0057] The curable resin composition of the present invention can be obtained by uniformly mixing the above-mentioned components in a predetermined ratio, and is usually pre-cured at 130 to 180° C. for 30 to 500 seconds, and then post-cured at 150 to 200° C. for 2 to 15 hours, so that the curing reaction proceeds sufficiently to obtain the cured product of the present invention. Alternatively, the components of the curable resin composition can be uniformly dispersed or dissolved in a solvent or the like, and cured after removing the solvent.
[0058] The curable resin composition of the present invention thus obtained has moisture resistance, heat resistance, and high adhesion. Therefore, the curable resin composition of the present invention can be used in a wide range of fields that require moisture resistance, heat resistance, and high adhesion. Specifically, it is useful as a material for all electrical and electronic components, such as insulating materials, laminates (printed wiring boards, BGA substrates, build-up substrates, etc.), sealing materials, and resists. It can also be used in the fields of molding materials, composite materials, paint materials, adhesives, 3D printing, and the like. In particular, solder reflow resistance is beneficial in semiconductor sealing.
[0059] The semiconductor device is encapsulated with the curable resin composition of the present invention. Examples of the semiconductor device include a DIP (dual in-line package), a QFP (quad flat package), a BGA (ball grid array), a CSP (chip size package), a SOP (small outline package), a TSOP (thin small outline package), and a TQFP (thin quad flat package).
[0060] The method for preparing the curable resin composition of the present invention is not particularly limited, but each component may be mixed uniformly or may be prepolymerized. For example, the maleimide compound represented by the formula (1) is prepolymerized by heating in the presence or absence of a catalyst and in the presence or absence of a solvent. Similarly, in addition to the maleimide compound represented by the formula (1), curing agents such as epoxy resins, amine compounds, maleimide compounds, cyanate ester compounds, phenolic resins, and acid anhydride compounds and other additives may be added to prepolymerize. For mixing or prepolymerization of each component, for example, an extruder, kneader, roll, etc. are used in the absence of a solvent, and a reaction kettle with a stirrer is used in the presence of a solvent.
[0061] As a method of uniformly mixing, the mixture is kneaded at a temperature in the range of 50 to 100°C using a device such as a kneader, roll, or planetary mixer to obtain a uniform resin composition. The obtained resin composition is crushed and then molded into a cylindrical tablet shape using a molding machine such as a tablet machine, or into a granular powder or powder molded body, or these compositions can be melted on a surface support and molded into a sheet with a thickness of 0.05 mm to 10 mm to obtain a molded curable resin composition. The obtained molded body is a non-sticky molded body at 0 to 20°C, and even if stored at -25 to 0°C for one week or more, the fluidity and curability are hardly reduced. The obtained molded article can be molded into a cured product using a transfer molding machine or a compression molding machine.
[0062] An organic solvent may be added to the curable resin composition of the present invention to form a varnish-like composition (hereinafter, simply referred to as varnish). The curable resin composition of the present invention may be dissolved in a solvent such as toluene, xylene, acetone, methyl ethyl ketone, methyl isobutyl ketone, dimethylformamide, dimethylacetamide, or N-methylpyrrolidone as necessary to form a varnish, which may then be impregnated into a substrate such as glass fiber, carbon fiber, polyester fiber, polyamide fiber, alumina fiber, or paper, and dried by heating to obtain a prepreg, which may then be hot-press molded to form a cured product of the curable resin composition of the present invention. The solvent used in this case is usually in an amount of 10 to 70% by weight, preferably 15 to 70% by weight, of the mixture of the curable resin composition of the present invention and the solvent. In addition, if the composition is in a liquid state, a cured product of the curable resin containing carbon fiber may be obtained as it is, for example, by the RTM method.
[0063] The curable composition of the present invention can also be used as a modifier for a film-type composition. Specifically, it can be used to improve flexibility in the B-stage. Such a film-type resin composition is obtained as a sheet-like adhesive by applying the curable resin composition of the present invention as the curable resin composition varnish onto a release film, removing the solvent under heating, and then performing B-stage formation. This sheet-like adhesive can be used as an interlayer insulating layer in a multilayer substrate or the like.
[0064] The curable resin composition of the present invention can be heated and melted to reduce the viscosity, and impregnated into reinforcing fibers such as glass fibers, carbon fibers, polyester fibers, polyamide fibers, and alumina fibers to obtain a prepreg. Specific examples thereof include glass fibers such as E glass cloth, D glass cloth, S glass cloth, Q glass cloth, spherical glass cloth, NE glass cloth, and T glass cloth, inorganic fibers other than glass, polyparaphenylene terephthalamide (Kevlar (registered trademark), manufactured by DuPont Co., Ltd.), fully aromatic polyamide, polyester, and organic fibers such as polyparaphenylene benzoxazole, polyimide, and carbon fibers, but are not particularly limited thereto. The shape of the substrate is not particularly limited, but examples thereof include woven fabric, nonwoven fabric, roving, chopped strand mat, and the like. In addition, as the weaving method of the woven fabric, plain weave, saddle weave, twill weave, and the like are known, and these known weaves can be appropriately selected and used depending on the intended use and performance. In addition, woven fabrics that have been subjected to fiber opening treatment and glass woven fabrics that have been surface-treated with a silane coupling agent or the like are preferably used. The thickness of the substrate is not particularly limited, but is preferably about 0.01 to 0.4 mm. A prepreg can also be obtained by impregnating reinforcing fibers with the varnish and drying the fibers by heating.
[0065] The laminate of this embodiment includes one or more of the prepregs. The laminate is not particularly limited as long as it includes one or more prepregs, and may include any other layer. The method for producing the laminate can be appropriately applied by a generally known method, and is not particularly limited. For example, when forming the metal foil-clad laminate, a multi-stage press machine, a multi-stage vacuum press machine, a continuous molding machine, an autoclave molding machine, or the like can be used, and the prepregs are laminated together and heated and pressurized to obtain a laminate. At this time, the heating temperature is not particularly limited, but is preferably 65 to 300°C, and more preferably 120 to 270°C. In addition, the pressure to be applied is not particularly limited, but if the pressure is too high, it is difficult to adjust the solid content of the resin in the laminate, and the quality is not stable, and if the pressure is too low, air bubbles and adhesion between the laminates are deteriorated, so that the pressure is preferably 2.0 to 5.0 MPa, and more preferably 2.5 to 4.0 MPa. The laminate of this embodiment includes a layer made of metal foil, and can be suitably used as a metal foil-clad laminate described later. The prepreg is cut into a desired shape and laminated with copper foil or the like if necessary. The laminate is then heated and cured while applying pressure thereto by press molding, autoclave molding, sheet winding molding, or the like, to obtain an electrical and electronic laminate (printed wiring board) or a carbon fiber reinforced material.
[0066] The cured product of the present invention can be used in various applications such as molding materials, adhesives, composite materials, coating materials, etc. The cured product of the curable resin composition of the present invention exhibits excellent heat resistance and dielectric properties, and is therefore suitably used for electrical and electronic parts such as encapsulants for semiconductor elements, encapsulants for liquid crystal display elements, encapsulants for organic EL elements, printed wiring boards, and build-up laminates, as well as lightweight, high-strength materials such as carbon fiber reinforced plastics and glass fiber reinforced plastics. EXAMPLES
[0067] The present invention will now be described in more detail with reference to examples. Unless otherwise specified, all parts are by weight. However, the present invention is not limited to these examples.
[0068] Various analytical methods used in the examples are described below. <Gel Permeation Chromatography (GPC)> The weight average molecular weight (Mw) and number average molecular weight (Mn) were calculated in terms of polystyrene using a polystyrene standard solution. GPC: DGU-20A3R, LC-20AD, SIL-20AHT, RID-20A, SPD-20A, CTO-20A, CBM-20A (all manufactured by Shimadzu Corporation) Column: Shodex KF-603, KF-602x2, KF-601x2) Eluent: Tetrahydrofuran Flow rate: 1ml / min. Column temperature: 40℃ Detection: RI (Differential Refractive Index Detector)
[0069] [Synthesis Example 1] A flask equipped with a thermometer, a condenser, a distillation tube, a stirrer, and a dropping funnel was purged with nitrogen while adding 100 parts of toluene, 58.8 parts of maleic anhydride, and 1 part of methanesulfonic acid, and the temperature was raised to reflux temperature. A separately prepared amine solution (a mixed solution of 50.9 parts of 4,4'-methylenebis(2,6-dimethylaniline) (KAYABOND C-200S: manufactured by Nippon Kayaku Co., Ltd.), 150 parts of NMP, and 50 parts of toluene) was added dropwise over 1 hour, and the mixture was allowed to react for 2 hours under reflux. The organic layer was washed twice with 100 parts of water, and the mixture was allowed to cool to precipitate crystals. The precipitated crystals were separated by filtration, and 47 parts of the target maleimide compound (M-1) was obtained as white crystals. The GPC chart of the obtained compound is shown in Figure 1. 1 The H-NMR (deuterated chloroform) chart is shown in Figure 2. A peak derived from a methyl group was observed at 2.11 ppm (s, 12H). A peak derived from a methylene bond was observed at 3.88 ppm (s, 2H). A peak derived from a maleimide group was observed at 6.87 ppm (s, 4H). A peak derived from an aromatic ring was observed at 6.98 ppm (s, 4H). From the above, the structure was identified as a maleimide derivative of 4,4'-methylenebis(2,6-dimethylaniline). [Synthesis Example 2] A flask equipped with a thermometer, a condenser, a distillation tube, a stirrer, and a dropping funnel was purged with nitrogen while adding 100 parts of toluene, 73.5 parts of maleic anhydride, and 2.6 parts of methanesulfonic acid, and the temperature was raised to reflux temperature. A separately prepared amine solution (a mixed solution of 64.1 parts of 4,4'-methylenebis(2-ethylaniline) (KAYAHARD AA: manufactured by Nippon Kayaku Co., Ltd.) and 40 parts of toluene) was added dropwise over 1 hour, and the mixture was allowed to react for 2 hours under reflux. The organic layer was washed twice with 100 parts of water, and the mixture was allowed to cool to precipitate crystals. The precipitated crystals were separated by filtration, and 50 parts of maleimide compound (M-2) were obtained as white crystals. The GPC chart of the obtained compound is shown in Figure 3. 1 The H-NMR (deuterated chloroform) chart is shown in Figure 4. Peaks derived from methyl groups were observed at 1.12 ppm (t, 6H) and 2.45 ppm (q, 4H). A peak derived from a methylene bond was observed at 4.03 ppm (s, 2H). A peak derived from a maleimide group was observed at 6.86 ppm (s, 4H). Peaks derived from an aromatic ring were observed at 6.90-7.30 ppm (m, 6H). From the above, the structure was identified as a maleimide compound of 4,4'-methylenebis(2-ethylaniline).
[0070] [Example 1, Comparative Examples 1 to 3] In Example 1 and Comparative Examples 1 and 2, the materials were mixed in the ratios shown in Table 1, kneaded in a mortar, and then cured in a vacuum press at 220°C for 2 hours while using cushion paper as a spacer to give a film thickness of 300 μm, to obtain a cured product. In Comparative Example 3, the materials were mixed in the ratios shown in Table 1, heated and melted in a metal container, poured directly into a mold, transfer molded at 175°C, and then cured at 160°C for 2 hours and 180°C for 6 hours, to obtain a cured product.
[0071] <Dielectric constant test / dielectric loss test> The test was conducted by the cavity resonator perturbation method using a 10GHz cavity resonator manufactured by ATE Co., Ltd. The test was conducted with a sample size of 1.7mm width x 100mm length, and a thickness of 300μm (in the case of transfer molding, the sample size was 1.7mm width x 100mm length, and a test piece with a thickness of 1.7mm was used). The same test piece was also placed in a 150℃ oven and subjected to a high temperature storage test in air for 24 hours, and the dielectric properties were evaluated again. The results are shown in Table 1.
[0072] [Table 1] In the table, "-" indicates that the data was not measured.
[0073] M-3: Bis(3-ethyl-5-methyl-4-maleimidophenyl)methane NC-3000-L: Biphenyl aralkyl type epoxy resin (manufactured by Nippon Kayaku Co., Ltd.) GPH-65: Biphenyl aralkyl type phenolic resin (manufactured by Nippon Kayaku Co., Ltd.) 2E4MZ: 2-ethyl-4-methylimidazole (curing accelerator, manufactured by Shikoku Kasei Co., Ltd.)
[0074] Example 1 was excellent in terms of low dielectric properties and dielectric properties after high-temperature storage tests. On the other hand, Comparative Examples 1 and 2 had good initial dielectric properties, but the dielectric tangent deteriorated after a heat resistance test at 150°C for 24 hours, and thus had problems with long-term use. [Industrial Applicability]
[0075] The curable resin composition of the present invention and its cured product are useful for applications such as insulating materials for electric and electronic components (highly reliable semiconductor encapsulating materials, etc.), laminates (printed wiring boards, BGA substrates, build-up substrates, etc.), adhesives (conductive adhesives, etc.), various lightweight and high-strength material applications including CFRP, paints, 3D printing, etc.
Claims
1. A curable resin composition containing a maleimide resin and an imidazole compound, The maleimide resin contains a maleimide compound represented by the following formula (1): The content of the maleimide resin in the total amount of the curable resin composition is 90% by weight or more and 99.9% by weight or less, a dielectric loss tangent at a frequency of 10 GHz measured at 25°C before and after a heat resistance test at 150°C for 24 hours of a cured product obtained by curing the curable resin composition is 0.005 or less; A curable resin composition characterized in that the dielectric tangent after the heat resistance test is the same as or lower than the initial value. 【Chemistry 1】
2. The curable resin composition according to claim 1, wherein the imidazole compound is 2-ethyl-4-methylimidazole.
3. The curable resin composition according to claim 1 or 2, which is used for electric / electronic parts.
4. The curable resin composition according to claim 1 or 2, which is used for a lightweight, high-strength material application.
5. A cured product obtained by curing the curable resin composition according to claim 1 .
Citation Information
Patent Citations
bismaleimide
JP1986093159A
Epoxy resin-bismaleimide thermosetting resin composition
JP1991070729A
Thermosetting resin composition
JP1992359911A
Prepreg and laminated board
JP2001294689A
Thermosetting resin composition, cured product, electronic component sealing material, and electronic component package
JP2018123194A